The Influence of Interactive Strategy and Student Motivation on Reading Comprehension ability of the Eighth grade Students of State Junior High School 3 of Rambang Dangku - Dwi Okti Silviana (Universitas PGRI Palembang, 2021)
This research was concerned with the The Influence of Interactive Strategy and Student Motivation on Reading Comprehension ability of the Eighth grade Students of State Junior High School 3 of Rambang Dangkuâ€. In this study 60 students of Eight grade students of SMPN 3 Rambang Dangku in the academic year 2020/2021 were chosen as samples by means of two stage random sampling. This study applied factorial research design. The data were collected by using questionaire and test. The data were analyzed by using Paired Sample t-test, Independent Sample t-test, and Two-Way ANOVA. The results showed that, first, there was a significant influence in studentsâ€™ reading comprehension taught by using intertactive strategy technique. Second, there was not any significant influence in studentsâ€™ reading comprehension taught by conventional teaching technique. Third, there was significant influence in studentsâ€™ reading comprehension students who have high and low learning motivation by using intertactive strategy technique and conventional teaching technique. Last, there is not any significant interaction effects of motivation on studentsâ€™ narrative text comprehension taught by using intertactive strategy technique and learning motivation towards the studentsâ€™ reading comprehension of SMPN 3 Rambang Dangku. So, intertactive strategy technique was effective for students who have high and low learning motivation.